2016
DOI: 10.2486/indhealth.2015-0087
|View full text |Cite
|
Sign up to set email alerts
|

HIV testing and attitudes among the working-age population of Japan: annual health checkups may offer an effective way forwards

Abstract: In Japan, Voluntary Counselling and Testing (VCT) for HIV has been recommended for people concerned about their infection risk, especially those in high-risk groups. Although HIV awareness has declined in this country somewhat during recent years, the number of newly-infected cases has been increasing. The purpose of the current study therefore, was to determine the prevalence of HIV testing, individuals’ reasons for being tested, and the overall acceptance of HIV testing among working-age Japanese. We utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Although most of the results were novel in Japan, my findings on waning public interest and inconsistent knowledge about HIV, barriers to testing and late testing, gaps and deficiencies in sex education, and obstacles to safer sex complement research in Japan by other authors ( Kihara et al, 2003 , Kihara et al, 2002 , Iwamuro, 2007 , Nosaka and Chigusa, 2008 , Japan International Cooperation Agency, 2010 , Horino et al, 2016 , Ishimaru et al, 2016 ). My data on how the swine flu pandemic of 2009 was a factor in curtailing HIV testing were also supported by Japan's National Institute of Infectious Diseases, which speculated that a reduction by 16% in HIV consultations and testing might have occurred for this reason ( National Institute of Infectious Diseases, 2010 ).…”
Section: Discussionmentioning
confidence: 51%
“…Although most of the results were novel in Japan, my findings on waning public interest and inconsistent knowledge about HIV, barriers to testing and late testing, gaps and deficiencies in sex education, and obstacles to safer sex complement research in Japan by other authors ( Kihara et al, 2003 , Kihara et al, 2002 , Iwamuro, 2007 , Nosaka and Chigusa, 2008 , Japan International Cooperation Agency, 2010 , Horino et al, 2016 , Ishimaru et al, 2016 ). My data on how the swine flu pandemic of 2009 was a factor in curtailing HIV testing were also supported by Japan's National Institute of Infectious Diseases, which speculated that a reduction by 16% in HIV consultations and testing might have occurred for this reason ( National Institute of Infectious Diseases, 2010 ).…”
Section: Discussionmentioning
confidence: 51%
“…Age was not found to be a predictive factor in the present study, a finding that was inconsistent with some other research conducted in Japan, which found that older age (≥40 years) was independently associated with decreased discriminatory attitudes, although the participants of that particular study were not healthcare workers) 30) . Nevertheless, employers will still need to consider the confidentiality of healthcare workers with infectious diseases to help these workers cope with potentially discriminatory attitudes 31) .…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, public health centers known as Hokenjo provide free and anonymous HIV testing. The Japanese AIDS Prevention guidelines recommend voluntary counseling and testing for high-risk groups [18]. However, HIV testing in Japan has decreased by 35% from 177,000 in 2008 to 118,000 in 2016 [19].…”
Section: Introductionmentioning
confidence: 99%